Expression of far upstream element (FUSE) binding protein 1 in human glioma is correlated with c‐Myc and cell proliferation. Issue 5 (17th December 2013) - Ding, Zongmei; Liu, Xiancheng; Liu, Yonghua; Zhang, Jianguo; Huang, Xianting; Yang, Xiaojing; Yao, Li; Cui, Gang; Wang, Donglin
Abstract Glioma is one of the most common type of primary intracranial tumor. Although great advances have been achieved in treatment of glioma, the underlying molecular mechanisms remain largely unknown. Previous studies demonstrated that FBP1 is a transcriptional regulator of c‐Myc and acts as an important prognostic indicator in many cancers. Our study aimed to assess the expression and function of FBP1 in human glioma. Immunohistochemical and Western blot analysis were performed in human glioma and normal brain tissues. High FBP1 expression (located in cell nuclei) was observed in 70 samples and its level was correlated with the grade of malignancy. A strongly positive correlation was observed between FBP1 and c‐Myc (P = 0.005) and Ki‐67 expression (P = 0.009). In a multivariate analysis, high FBP1 and c‐Myc expressions were showed to be associated with poor prognosis in glioma. While in vitro, following serum stimulation of starved U87MG cells, the expression of FBP1 was upregulated, as well as c‐Myc and PCNA. Moreover, knockdown of FBP1 by siRNA transfection diminished the expression of c‐Myc and arrested cell growth at G1 phase. Collectively, our results shows that the expression of FBP1 is in close correlation with c‐Myc level and cell proliferation in glioma and provides a potential strategy to develop FBP1 inhibitors as novel anti‐tumor agents. © 2013 Wiley Periodicals, Inc.